2-Acetamidobenzonitrile - Arslan, B; Kazak, C; Kirilmis, C; Koca, M; Büyükgüngör, O (Int Union Crystallography, 2005)
The title compound, C9H8N2O, was synthesized from 2-cyanoaniline and acetyl chloride in dry acetone. The crystal structure is stabilized by an intramolecular C-H center dot center dot center dot O hydrogen-bond contact, which forms a six-membered ring, and two intermolecular N-H center dot center dot center dot N and C-H center dot center dot center dot O hydrogen bonds.